Acylation and cholesterol binding are not required for targeting of influenza A virus M2 protein to the hemagglutinin‐defined budozone. Issue 6 (20th February 2014) - Thaa, Bastian; Siche, Stefanie; Herrmann, Andreas; Veit, Michael
Abstract : Influenza virus assembles in the budozone, a cholesterol‐/sphingolipid‐enriched ("raft") domain at the apical plasma membrane, organized by hemagglutinin (HA). The viral protein M2 localizes to the budozone edge for virus particle scission. This was proposed to depend on acylation and cholesterol binding. We show that M2–GFP without these motifs is still transported apically in polarized cells. Employing FRET, we determined that clustering between HA and M2 is reduced upon disruption of HA's raft‐association features (acylation, transmembranous VIL motif), but remains unchanged with M2 lacking acylation and/or cholesterol‐binding sites. The motifs are thus irrelevant for M2 targeting in cells. Abstract : The budozone, organized by hemagglutinin, is a large, stabilized membrane raft. Acylation and cholesterol binding have been proposed to target M2 to the budozone. FRET shows that the raft‐targeting features are irrelevant for HA–M2 clustering. These features are also not involved in apical targeting of M2.